34th Malaysian Association of Clinical Biochemists Annual Conference in collaboration with 2nd Malaysian Biomedical Science Association Symposium 2024 - Wan Amir Nizam Wan Ahmad; Seri Narti Edayu Sarchio; Nur Najmi Mohamad Anuar; Nor Fadilah Rajab; Suvik Assaw; Rhun Yian Koh; Chooi Ling Lim; Nur Aishah Sharudin; Norlida Harun; Nurulamin Abu Bakar; Mohd Arifin Kaderi (Life Sciences, Medicine and Biomedicine)
The Malaysian Association of Clinical Biochemists (MACB) and the Malaysian Biomedical Science Association (MyBiomed) successfully organized the 34th MACB Conference in conjunction with the 2nd MyBiomed Symposium 2024. Under the theme 'Towards Holistic Integration and Sustainability in Medical Laboratories, the event brought together experts from various disciplines to explore advancements and sustainability in laboratory medicine and biomedical science. The conference featured a comprehensive program including plenary lectures, industrial talks, oral and poster presentations, and trade exhibitions. It provided a platform for the exchange of scientific knowledge and insights into emerging technologies and practices. A diverse range of professionals participated, including local and international chemical pathologists, clinical biochemists, medical laboratory scientists, researchers, and postgraduate students. Key topics covered included natural product research, herbs and metabolic disease, molecular diagnostics, pharmacology and toxicology, endocrinology, reference intervals, value-based laboratory medicine, newborn screening, the role of digital technologies in medical labs, and strategies for developing green & sustainable medical laboratories. The discussions were aligned with the conference’s goal of fostering integration and sustainable practices in the medical laboratory sector, reflecting the latest trends and future directions of the field. The event achieved its aim of providing participants with valuable updates on scientific and technological innovations while fostering collaboration and dialogue among laboratory professionals at a global scale.